2015
DOI: 10.1007/s00240-015-0755-7
|View full text |Cite
|
Sign up to set email alerts
|

‘X-ray’-free balloon dilation for totally ultrasound-guided percutaneous nephrolithotomy

Abstract: The objective of the study was to evaluate the feasibility and safety of balloon dilation for 'X-ray'-free ultrasound-guided percutaneous nephrolithotomy (PCNL). From January 2012 to December 2012, patients underwent 'X-ray'-free ultrasound-guided PCNL with Amplatz dilator (Group A). From January 2013 to April 2014, patients underwent 'X-ray'-free ultrasound-guided PCNL with balloon dilator (Group B). For balloon dilation, a 10 F fascial dilator was used to dilate the tract. Subsequently, the 6 F nephrostomy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 13 publications
1
29
1
Order By: Relevance
“…These include the use of Teflon dilators 25 ; a small scope to confirm proper dilator placement 7 ; and more recently, balloon dilators to perform radiation-free US-guided PCNL. 26 All of these studies demonstrate the power of how US can be used to guide the process of renal tract dilation, a technical step of PCNL that has been relatively understudied.…”
Section: Discussionmentioning
confidence: 96%
“…These include the use of Teflon dilators 25 ; a small scope to confirm proper dilator placement 7 ; and more recently, balloon dilators to perform radiation-free US-guided PCNL. 26 All of these studies demonstrate the power of how US can be used to guide the process of renal tract dilation, a technical step of PCNL that has been relatively understudied.…”
Section: Discussionmentioning
confidence: 96%
“…There are few studies concerning balloon dilation method in totally ultrasound-guided PCNL in the literature. Ren et al compared the outcomes of PCNL using two tract dilation methods under unltrasound guidance and concluded that BD had a higher success rate of access creation and less blood loss [23].Zhou et al suggested that BD was preferable for beginners because it was associated with less hemorrhage complication compared with that of Amplatz dilation [24]. However, we failed to find any significant difference between two groups regarding blood loss and complication in this study; The Hb drop was mainly caused by hemodilution.…”
Section: Discussionmentioning
confidence: 99%
“…The steps of channel establishment are mainly divided into puncture and dilation, which requires the surgeon to accurately puncture and rapidly dilate [12,13]. Generally, puncture is guided in vitro by X-ray or US [12,14]. Since US is not only free from contrast agents, but also bene cial for identi cation of important blood vessels including renal artery, vein and arcuate arteries, we adopted US-guided puncture.…”
Section: Discussionmentioning
confidence: 99%